Low‐value injury admissions in an integrated Canadian trauma system: A multicentre cohort study. Issue 10 (11th July 2021) - Gagnon, Marc‐Aurèle; Bérubé, Mélanie; Mercier, Éric; Yanchar, Natalie; Cameron, Peter; Stelfox, Thomas; Gabbe, Belinda; Bourgeois, Gilles; Lauzier, François; Turgeon, Alexis; Belcaid, Amina; Moore, Lynne
Abstract: Background: Injury represents 260 000 hospitalisations and $27 billion in healthcare costs each year in Canada. Evidence suggests that there is significant variation in the prevalence of hospital admissions among emergency department presentations between countries and providers, but we lack data specific to injury admissions. We aimed to estimate the prevalence of potentially low‐value injury admissions following injury in a Canadian provincial trauma system, identify diagnostic groups contributing most to low‐value admissions and assess inter‐hospital variation. Methods: We conducted a retrospective multicentre cohort study based on all injury admissions in the Québec trauma system (2013‐2018). Using literature and expert consultation, we developed criteria to identify potentially low‐value injury admissions. We used a multilevel logistic regression model to evaluate inter‐hospital variation in the prevalence of low‐value injury admissions with intraclass correlation coefficients (ICC). We stratified our analyses by age (1‐15; 16‐64; 65‐74; 75+ years). Results: The prevalence of low‐value injury admissions was 16% (n = 19 163) among all patients, 26% (2136) in children, 11% (4695) in young adults and 19% (12 345) in older adults. Diagnostic groups contributing most to low‐value admissions were mild traumatic brain injury in children (48% of low‐value paediatric injury admissions; n = 922), superficial injuries (14%, n = 660) or minor spinal injuries (14%, n = 634) in adults aged 16‐64 and superficial injuries in adults aged 65+ (22%, n = 2771). We observed strong inter‐hospital variation in the prevalence of low‐value injury admissions (ICC = 37%). Conclusion: One out of six hospital admissions following injury may be of low value. Children with mild traumatic brain injury and adults with superficial injuries could be good targets for future research efforts seeking to reduce healthcare services overuse. Inter‐hospital variation indicates there may be an opportunity to reduce low‐value injury admissions with appropriate interventions targeting modifications in care processes.